South Sutter Water District - a case study of an agricultural and urban partnership - Harper, Sara F., author; Van Camp, Marc, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The following case study describes a partnership between an agricultural water supplier, South Sutter Water District (District), and various State Water Contractors built through the development and execution of a water transfer. In 2008, the District considered the possibility of a water transfer due to the increased costs associated with the Federal Energy Regulatory Commission relicensing process, the US Army Corps of Engineers' requirement relative to the restructuring of the Reservoir spillway to meet criteria for the Probable Maximum Flood, and other regulatory and general cost increases. In order for the District to offset a portion of these significant expenses and maintain an affordable surface water supply for its landowners, the District elected to participate in its first water transfer with the State Water Contractors. Due to the unique nature of the transfer, which included a reservoir release and an increase in groundwater use to meet local demand, this 2008 Pilot Water Transfer was considered. Ultimately, 6,909 acre-feet of water was transferred from the District to participating State Water Contractor agencies.
USCID water management conference
Agricultural and urban partnership
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.